Pelatihan Budidaya Tanaman Hidroponik untuk Peningkatan Keterampilan dan Kreativitas Anak Sekolah Alam Aminah - Putri Permatasari; Agung Wibowo; Suwarto Suwarto; Arip Wijianto; Amalia Nadifta Ulfa (Jurnal Surya Masyarakat, 2026)
Plant cultivation using the hydroponic system has many advantages with planting techniques without using soil media so that it is suitable for application in limited land. The hydroponic farming system can be introduced to students as a form of environmental learning. One of the educational institutions that implements environmental-based learning is the Aminah Nature School in Sukoharjo Regency, Central Java. The purpose of the community service activities carried out by the Universitas Sebelas Maret Agricultural Extension Research Group is to provide assistance to students so that their knowledge and skills increase in their ability to apply plant cultivation using the hydroponic method. The method of implementing activities with several stages includes preparation, implementation and evaluation of activities. Preparation is carried out by identifying problems, discussions and coordination as well as preparation for making training materials. Implementation of activities by conducting socialization and training for students about the hydroponic farming system in cultivating pakcoy vegetables. Training is also carried out by inviting students to practice directly in making a simple hydroponic farming system installation by utilizing plastic bottle waste. The activities that have been carried out are then evaluated to assess the extent of the success of the implementation of the activities and can be used as material for improvement for subsequent activities. This mentoring activity is expected to increase students' awareness of environmental management and increase their creativity in processing waste into useful items.